CuII Ion Doping Enhances the Water Stability of Luminescent Metal–Organic Framework, Realizing the Detection of Fe3+ and Antibiotics in Aqueous Solutions - Jia, Ruo-Qin; Tan, Geng; Chen, Ying-Jun; Zuo, Lu-Yang; Li, Bo; Wang, Li-Ya (Frontiers in Chemistry, 2022)
Luminescent metal-organic frameworks (LMOFs) have been widely developed in the field of chemical sensing owing to their outstanding photoluminescence performance, high selectivity, anti-interference, high sensitivity and fast response, and become one of the research hotspots of emerging functional materials. However, in practical application, many tests are carried out in the water environment, fragile water stability greatly limits the application of MOFs in the field. Therefore, it is important to develop a method to enhance the water stability of MOFs. Herein, a new complex {[Zn(L)]•CH3CN}n (Zn-MOF, H2L = 5-(benzimidazol-1-yl) isophthalic acid) with superior photophysical property has been synthesized firstly. Its water stability was highly enhanced by the doping CuII ions by one-pot method. In addition, the detection performance of doping material Cu0.1/Zn-MOF for sixteen metal ions and thirteen antibiotics were well studied. It was found that Cu0.1/Zn-MOFs displays high sensitivity, fast response, lower detection limit and long-term stability for the detection of Fe3+, NFT, NFZ, FZD and TC in aqueous medium.